-8-(6-8m)=2(m-1)

Simple and best practice solution for -8-(6-8m)=2(m-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-(6-8m)=2(m-1) equation:



-8-(6-8m)=2(m-1)
We move all terms to the left:
-8-(6-8m)-(2(m-1))=0
We add all the numbers together, and all the variables
-(-8m+6)-(2(m-1))-8=0
We get rid of parentheses
8m-(2(m-1))-6-8=0
We calculate terms in parentheses: -(2(m-1)), so:
2(m-1)
We multiply parentheses
2m-2
Back to the equation:
-(2m-2)
We add all the numbers together, and all the variables
8m-(2m-2)-14=0
We get rid of parentheses
8m-2m+2-14=0
We add all the numbers together, and all the variables
6m-12=0
We move all terms containing m to the left, all other terms to the right
6m=12
m=12/6
m=2

See similar equations:

| 51=5(3a+6)-8 | | 7(4-4x)=-8(1+3x) | | 30.25x=60 | | 17=3-2(2f-1) | | 5x+3–3x+2=35 | | -(7x-1)+14=21 | | 8+w/2=11 | | 0.05x=37.25 | | 2m=78 | | 13-3k=7 | | 26+4.25.x=60 | | -3(-6b-4)=6(4b+6) | | -6u-36=−42 | | -4(m-1)=-8 | | -6u-36= | | 16/4=v | | 9.43=k−9.64 | | 2(4x+2)+x=9x-4 | | 30+x=3/5 | | 19t-16t=48 | | 3/4(8x−12)=4x−4 | | 72=27+9s | | 2.25p+14=1.50p+20 | | 24t-14t=54 | | 2(-5x+4)+4x-5=-3 | | −60=24+12r | | y=41.7(298.2) | | z=7(9) | | 11t+9t=5 | | 7x^2+69+54=0 | | 8t+7t=225 | | 150+1/2g=120+1/4g |

Equations solver categories